Unraveling the relationship between work pressure, work environment, and turnover intentions: a study at alfamart - Maulana, Yogi; Pariyanti, Eka; Aliyah, Himatul (Enrichment : Journal of Management, 2024)
The aim of this research is to explore the influence of work pressure and work environment on turnover intention of Alfamart employees. The method used is multiple linear regression analysis of survey data from Alfamart employees. The results of the analysis show that both factors, work pressure and work environment, have a significant influence on employee turnover intention. Work pressure is positively related to turnover intention, while the work environment is negatively related. The interaction between work pressure and work environment also influences turnover intention significantly. The implication of these findings is the importance of Alfamart management to pay attention to these two factors in an effort to reduce employee turnover rates. By improving work pressure conditions and improving the quality of the work environment, employee retention and workforce stability at Alfamart can be increased